Utilization of the complete blood count in diagnosing endemic diseases in Pakistan - Khalid, Noor; Umer, Muhammad (Journal of the Pakistan Medical Association, 2023)
Numerous infectious diseases, including enteric fever, malaria, dengue fever, and, most recently, coronavirus disease-2019, are prevalent in Pakistan. All these diseases have overlapping clinical symptoms and can present a diagnostic challenge for the general practitioner. Since definitive testing for these disorders is time-consuming and expensive, basic clinical testing, such as a complete blood count, should be utilised to supplement clinical diagnosis, when possible. The current narrative review was planned to present specific alterations in haematological parameters for each of these disorders. The review was intended as a guide for practising physicians in their decision-making. Key Words: Complete blood count, Typhoid fever, Malaria, Dengue, COVID-19.